Sistema Web para Mejorar la Oferta Turística en el Ecuador - Muñoz Moran, Joel Ricardo (2018)
Ecuador owes a large part of its annual income to the tourism sector; main economic engine with medium and long-term expectations. The Ministry of Tourism (Mintur) through the Quality Department and in compliance with its competences, seeks the implementation of the National Tourism Quality System (SNCT) with the objective of promoting a culture of excellence that allows Ecuador to position itself as a Tourist Power in the national and international markets, and the provision of a quality service is the differentiating feature, for which, the Ministry of Tourism of Ecuador established clear and well-defined objectives, among which are: Increase the participation of tourism in the national economy; increase efficiency and effectiveness in the performance of judicial processes, administrative procedures and advice; increase the availability of information related to tourism markets, the industry, the marketing chain and the economic impact of the sector, aligned with the execution of the National Plan for Good Living; increase the supply of quality tourist services at a national level, etc. (Ecuador, Ministry of Tourism - Ecuador, 2018) Mainly, potential tourists look for relevant information regarding services, points of interest, lodging, etc. Before making the decision to visit a specific country, they need all kinds of data that allows them to have a clear and well-founded idea of ​​where they want to visit and which one is more convenient according to their needs. Within this scope, the country needs an online system that allows its potential visitors to access from any part of the world to strictly structured and constantly updated information, from the geographical point they want to reach and the relevance of the environment. This work is aimed at developing the prototype of a web system to improve the tourist offer in Ecuador, with the purpose of developing a premium tool able to solve the needs of users seeking a reliable conceptual source. The prototype aims to lay the foundations for the development and subsequent application of a versatile and dynamic system, focused on the correct management and presentation of data from the tourism sector of Ecuador.